IDIOMS IN THE PROSE WRITINGS OF TURKISH AUTHORS FROM NORTH MACEDONIA - H. Skuka (Trakia Journal of Sciences)
Over centuries, the Macedonian language, influenced by Turkish, has absorbed not only Turkish words and phrases but also numerous idioms. Some of these idioms were translated word for word, some were adapted by translating a single word, while others were directly incorporated, and some were translated into Macedonian using words that roughly convey their original meaning.Over time, the meanings of some of these idioms have changed or diversified. Following the onset of an influence, or rather, an influence in the opposite direction –namely, the impact of Macedonian on the language of the Macedonian Turks –these idioms, which underwent changes, began to settle into the language of the Turkish community in North Macedonia. Consequently, the MacedonianTurks haveforgotten the original meanings and forms of their idioms and have adopted their altered meanings and forms from the Macedonian language.The subject of this study is Turkish idioms that have lost their original meanings and forms when used in the writtenlanguage of the Macedonian Turks. For this purpose, certain prose writings by Macedonian Turkish writers have been examined, errors in the use of idioms encountered there have been identified, and their original meanings and correct usage have been demonstrated. As a result, it has been determined that some of the errors in the use of Turkish idioms stem from their adoption of altered meanings and forms in the Macedonian language, some from misconceptions about the meanings carried by the idioms, and others from the consistent misuse of the second verb in idiomatic expressions formed by semantic shifts.